LEITURAS SOBRE OS “AWÁ DA MATA - CORDEIRO, Zeneide Pereira (2024)
This thesis is a study on the current situation of the Awá da mata, an indigenous people classified by Funai as "isolated" who inhabit the Araribóia, Awá, Caru and Alto Turiaçu Indigenous Lands, demarcated and homologated, located in the Maranhão Amazon. The information about this people was constructed from reports of contacts between the "Awá da mata" and the Tentehar/Guajajara, an indigenous people with whom they share territory, and with non-indigenous people who established different forms of contact with them. Among the non- indigenous people are loggers, fishermen, farmers, businessmen and squatters. The field research took place in the Araribóia Indigenous Land and in centers, villages and municipalities located near the Araribóia, Alto Turiaçu Indigenous Land, Awá Indigenous Land and Caru Indigenous Land. It was not possible to conduct research directly with the "Awá of the forest" due to the difficulty of approaching and even locating these groups who are constantly moving and assume a withdrawn posture. The data construction instruments were largely accessibility resources, some adapted according to my needs as a blind woman, such as canes, screen readers and mind maps. These resources are the means that allow me to know and apprehend any information in the world. The first procedures I performed before going to the field were to build networks of contacts, taking as a starting point, agents with whom I have family relationships, friendships, interests and political positions, beliefs, and artistic and cultural tastes. I used informal conversations through online social networks with various agents, indigenous people, settlers, rural workers, businessmen, religious people, etc. In my relationship with my interlocutors, during the field research, I was able to understand that what I designated as "isolated", the Awá already contacted defined as "people of the forest" and the Guajajara or a non-indigenous person, designated as "brabo". So I chose to use the category "Awá of the forest", in an approximation of the denomination "people of the forest" created by the contacted Awá . The "Awá of the forest" live in constant threat, suffer physical and territorial violence justified by three types of dehumanization of the Awá; the "brabos", "capilobo" and "encantados". The squatters, farmers and residents of centers, riverbanks and villages justify the invasion and the violence carried out against these people as a need to free up the land for hunting, fishing and planting crops to eat. The Guajajara call the Awá "brabos" and claim that the Araribóia Indigenous Land is not the territory of the "brabos", who are considered as "inferior people", but the exclusive territory of the Guajajara. Non-indigenous people refer to the "Awá of the forest" as "wild" with the aim of denying Awá humanity , also believing that the Awá are monsters and mystical or enchanted beings. In this last sense, the Awá would be neither animals nor humans. During the research, I built a new identity through an intertwining of social, spiritual and territorial relationships, initially by my grandparents. I began the field by seeking to identify my Awá origins. Being among the Guajajara, I came to be considered a Guajajara, which excluded my kinship with the Awá. This was extremely important for my understanding of some aspects of the relations between the Guajajara and the Awá "of the forest" in the Araribóia Indigenous Land.